2021
DOI: 10.3389/fvets.2021.664226
|View full text |Cite
|
Sign up to set email alerts
|

Pigeons as Carriers of Clinically Relevant Multidrug-Resistant Pathogens—A Clinical Case Report and Literature Review

Abstract: Pigeons are widespread bird species in urban regions (Columba livia forma urbana) and may carry pathogens with zoonotic potential. In recent years, more and more data indicate that these zoonotic pathogens are multidrug resistant. Our results confirmed that global trend. Three different multidrug-resistant pathogens were isolated from an oral cavity of a racing pigeon with lesions typical for pigeon pox virus infection. Staphylococcus aureus was recognized as methicillin resistant, thus resistant to all beta-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…in pigeons (Hosain et al 2012;Dey et al 2013;Bupasha et al 2020). These birds may have acquired MDR strains via eating food and water polluted with human feces and farm waste, misusing antibiotics, and transmitting these bacteria to humans and other animals (Borges et al 2017;Karim et al 2020;Chrobak-Chmiel et al 2021). According to our study, isolated bacteria showed highest sensitivity to GEN (83.1%), followed by LEV (81.5%), CIP (80.4%), KAN (77.8%), and CFM (59.3%).…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…in pigeons (Hosain et al 2012;Dey et al 2013;Bupasha et al 2020). These birds may have acquired MDR strains via eating food and water polluted with human feces and farm waste, misusing antibiotics, and transmitting these bacteria to humans and other animals (Borges et al 2017;Karim et al 2020;Chrobak-Chmiel et al 2021). According to our study, isolated bacteria showed highest sensitivity to GEN (83.1%), followed by LEV (81.5%), CIP (80.4%), KAN (77.8%), and CFM (59.3%).…”
Section: Discussionmentioning
confidence: 71%
“…The potential of zoonotic infections spreading to people through close contact with pigeons at home, in live bird markets, and on farms is high. To date, 110 zoonotic agents have been identified from pigeons (Hosain et al 2012;Teske et al 2013;Contreras et al 2016;Bupasha et al 2020;Chrobak-Chmiel et al 2021). The presence of methicillin-resistant staphylococci and other multidrug-resistant (MDR) zoonotic infection in pigeons is worrisome, as these pathogens may disperse across a large geographical region due to extensive distances travelled during racing flights (Chrobak-Chmiel et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…S. intermedius is described in the literature as a commensal bacterium of wild pigeons, whereas S. delphini colonizes members of the Mustelidae family, as well as dolphins and domestic pigeons. 6,11,25 Interestingly, S. intermedius and S. delphini have been isolated from raccoons ( Procyon lotor ), another member of the Procyonidae family, but at a much lower frequency. 18,20 Therefore, the present study suggests that coatis are natural hosts for SIG.…”
Section: Discussionmentioning
confidence: 99%